Spotlight on NLRP6 and Tumor Research Situation: A Potential Cancer Participant - Liangzheng Chang; Yuying Tian; Lei Xu; Qiuyao Hao; Lingyu Song; Yinying Lu; Yunhuan Zhen (Journal of Immunology Research)
NOD-like receptor family pyrin domain containing 6 (NLRP6) is a new pattern recognition receptor in the mammalian innate immune system. Both the liver and the gut exhibit substantial levels of cytoplasmic expression. It can speed up cell response to endogenous danger signals or exogenous pathogen infection. NLRP6 can function in various ways as an inflammasome or a noninflammasome. The understanding of NLRP6 is steadily increasing thanks to ongoing investigations, but due to discrepancies in how those studies have described their link with tumors, the significance of NLRP6 in the emergence of cancer is still debatable as of this writing. This article will use the structure and function of NLRP6 as the pivotal point and thoroughly explain the present interactions between NLRP6 and tumors and any possible clinical benefits.